Psilocybe chuxiongensis, a new bluing species from subtropical China - Ma, Tao; Feng, Ying; Lin, Xiao-Fei; Karunarathna, Samantha C.; Ding, Wei-Feng; Hyde, Kevin D. (Phytotaxa, 2014)
A new bluing species of Psilocybe in sect. Caerulescentes is described from subtropical China. It is closely related to P. cubensis but can be differentiated by the lack of an annulus and the buff-yellow to yellowish brown, hemispheric to hemispheric-convex pileus without an umbo or papilla. Phylogenetic analyses of ITS, nrLSU and combined rpb2-tef1-α datasets using maximum parsimony and Bayesian inference also indicate its uniqueness. The relationship with P. cubensis is well-supported by molecular data with high support values in all three datasets. Psilocybe chuxiongensis sp. nov. is presented here with a description, photographs, and line drawings.